PEMANFAATAN KULIT UDANG UNTUK PEMBUATAN KITOSAN DAN GLUKOSAMIN - Muhammad Hanafi; Syahrul Aiman; D Efrina; B. Suwandl (Jurnal Kimia Terapan Indonesia, 2000)
Shrimp shells as side product of frozen shrimp industry isnot yet used in pharmaceutical or chemical industries. Shrimpshells has a chemical constituent called chitin, calcium carbonateand protein as main compounds. By decalcination in dilute aqueosHCl solution (1-2 N) and deproteination ill dilute aqueos NaOHsolution (3-4 Nj gives a chitin. Deacetylation of chitin in theexcess of aqueous 50 % NaOH solution produces chitosan. Inthe preleminary experiment indicated that water (< 10%) andash (< 2%) content of chit os an same as standard. Based on theexperiment result the optimum condition was obtained as 1N HCIsolution (1: 10), 3N NaOH solution (1:6) and 50 % NaOH solution(1: 5) resulted 12,61 % chitosan with deacetylation degree valueabout 70 % with FT1R methode. Hydrolysis of chitin or chitosanin excess HCl gives glucosamine about 17 %, it's a mixture of aand B-glucosa11line. Glucoseamine is identified using 1H and13C NMR spectrum.